CNC Milling Maintenance Risk Prioritization Using FMEA Analysis: Penentuan Prioritas Risiko Pemeliharaan Mesin Penggilingan CNC Menggunakan Analisis FMEA - Ardiansyah Eko Saputra; Tedjo Sukmono (Indonesian Journal of Innovation Studies, 2026)
General Background CNC milling machines play a critical role in manufacturing by producing high-precision components, yet frequent component failures can disrupt production continuity. Specific Background At PT. IJA Surabaya, repeated breakdowns in CNC milling machines have led to decreased productivity and increased downtime. Knowledge Gap Existing maintenance practices lack structured risk prioritization to identify critical components and failure modes systematically. Aims This study aims to analyze machine maintenance using Failure Mode and Effects Analysis to determine priority risks and propose preventive actions. Results The findings indicate that the spindle component has the highest Risk Priority Number of 933, followed by air supply at 882 and drill bits at 714, mainly caused by inadequate lubrication, overloading, and improper usage. Novelty This study provides a structured application of FMEA in identifying critical maintenance priorities specifically in CNC milling operations within a real industrial setting. Implications The results support the development of preventive maintenance strategies, including routine lubrication scheduling, load monitoring, and periodic component replacement to reduce downtime and improve operational reliability. Keywords: Cnc Milling, Fmea Analysis, Machine Maintenance, Risk Priority Number, Preventive Maintenance Key Findings Highlights Spindle component shows the highest failure priority based on risk scoring Air system instability contributes significantly to operational disruption Tool wear patterns indicate need for scheduled replacement planning